STRATEGI MENINGKATKAN PENDAPATAN DI ERA DIGITALISASI: STUDI KASUS PLATFORM TIKTOK - Umi Nur Habibah; Nopita Sari Dewi Harahap; Hanifa Salsabila; Arie Satria Tama; Nurbaiti (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This research aims to inform the usefulness of the TikTok platform to increase revenue in the era of digitalization. This research method uses a literature review that analyzes various materials regarding revenue increase strategies on TikTok. TikTok now has hundreds of millions of users around the world, including Indonesia, and has grown from an entertainment platform to a strategic medium for branding and marketing. The results show that TikTok can earn income through content creators and businesses by using features such as video content, live streaming, and affiliate programs. So it is necessary to develop content that is interesting for content creators and business people so that the audience does not feel bored and still feels present in using TikTok.